2007
DOI: 10.1164/rccm.200607-947oc
|View full text |Cite
|
Sign up to set email alerts
|

Higher Urine Nitric Oxide Is Associated with Improved Outcomes in Patients with Acute Lung Injury

Abstract: Rationale: Nitrogen oxide (NO) species are markers for oxidative stress that may be pathogenic in acute lung injury (ALI). Objectives: We tested two hypotheses in patients with ALI: (1 ) higher levels of urine NO would be associated with worse clinical outcomes, and (2 ) ventilation with lower VT would reduce urine NO as a result of less stretch injury. Methods: Urine NO levels were measured by chemiluminescence in 566 patients enrolled in the National Heart Lung and Blood Institute Acute Respiratory Distress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Our findings may also provide a rationale for the treatment of pulmonary oedema with exogenous NO or NO donors in order to restore normal endothelial NO levels. Interestingly, acute lung injury patients with higher urinary NO levels had reduced mortality and patients experienced more ventilator-free days and more organ failure-free days [28]. Finally, our observations raise the hypothesis that interference with ASM activity inside caveolae may explain some of the short-term effects of steroids.…”
Section: Discussionmentioning
confidence: 51%
“…Our findings may also provide a rationale for the treatment of pulmonary oedema with exogenous NO or NO donors in order to restore normal endothelial NO levels. Interestingly, acute lung injury patients with higher urinary NO levels had reduced mortality and patients experienced more ventilator-free days and more organ failure-free days [28]. Finally, our observations raise the hypothesis that interference with ASM activity inside caveolae may explain some of the short-term effects of steroids.…”
Section: Discussionmentioning
confidence: 51%
“…44 Nitrogen oxide (NO) species are markers of oxidative stress, and are modulated by HMG-CoA reductase inhibitors. 45 Endotoxin and inflammatory cytokines activate inducible NO synthase and prolong NO production, which causes hypotension, decreased vasopressor response, and a tendency for multi-organ failure in sepsis, whereas they decrease eNOS. 46,47 A recent, multicenter study by McClintock et al 45 found that higher urine NO level was associated with better survival, and they suggested that higher NO level is associated with less severe pulmonary and systemic endothelial injury, as indicated by more ventilator-free days and organ-failure free days.…”
Section: Histopathology Analysismentioning
confidence: 99%
“…In a large randomized controlled trial of lower-vs. higher-tidal volume ventilation, urine levels of the NO products nitrate and nitrite were higher in survivors than non-survivors and rose more between enrollment and day 3 in patients treated with a low-tidal volume protective ventilatory strategy compared with patients treated with a higher-tidal volume ventilatory strategy (11). These data suggest that preserved NO production is an important marker of better outcomes in acute lung injury that is improved with a protective ventilator strategy.…”
mentioning
confidence: 76%